An Intimate History of the Front - Crouthamel, J. author. aut Link
XIII, 233 p.
Keywords: This eye-opening study gives a nuanced, provocative account of how German soldiers in the Great War experienced and enacted masculinity. Drawing on an array of relevant narratives and media, it explores the ways that both heterosexual and homosexual soldiers expressed emotion, understood romantic ideals, and approached intimacy and sexuality.